Lipids as a key element of insect defense systems - Wrońska, Anna Katarzyna; Kaczmarek, Agata; Boguś, Mieczysława Irena; Kuna, Anna (Frontiers in Genetics, 2023)
The relationship between insect pathogenic fungi and their insect hosts is a classic example of a co-evolutionary arms race between pathogen and target host: parasites evolve towards mechanisms that increase their advantage over the host, and the host increasingly strengthens its defenses. The present review summarizes the literature data describing the direct and indirect role of lipids as an important defense mechanism during fungal infection. Insect defense mechanisms comprise anatomical and physiological barriers, and cellular and humoral response mechanisms. The entomopathogenic fungi have the unique ability to digest the insect cuticle by producing hydrolytic enzymes with chitin-, lipo- and proteolytic activity; besides the oral tract, cuticle pays the way for fungal entry within the host. The key factor in insect resistance to fungal infection is the presence of certain types of lipids (free fatty acids, waxes or hydrocarbons) which can promote or inhibit fungal attachment to cuticle, and might also have antifungal activity. Lipids are considered as an important source of energy, and these (triglycerides) are stored in the fat body, a structure analogous to the liver and adipose tissue in vertebrates. In addition, the fat body plays a key role in innate humoral immunity by producing a range of bactericidal proteins and polypeptides, one of which is lysozyme. Energy derived from lipid metabolism is used by hemocytes to migrate to the site of fungal infection, and for phagocytosis, nodulation and encapsulation. One polyunsaturated fatty acid, arachidonic acid, is used in the synthesis of eicosanoids, which play several crucial roles in insect physiology and immunology. Apolipoprotein III is important compound with antifungal activity, which can modulate insect cellular response and is considered as important signal molecule.